Exploring plant species richness along the Tiber River within the city of Rome - Ceschin, Simona; Salerno, Giovanni (Phytotaxa, 2021)
The Tiber River stretch crossing the metropolitan area of Rome (Italy) is regarded as one of the main biological corridors of the city, as it diversifies the urban landscape while contributing to the plant diversity. This paper aims to document the current plant richness occurring along the Tiber within the city by providing a comprehensive inventory of the spontaneous vascular flora and an overview of its composition, and structural, chorological and ecological features. This flora lists 493 species and it is characterized by: i) high species richness (more than 30% of Rome’s flora), ii) presence of species with naturalistic value, as rare or included in Red List IUCN categories, iii) high number of ruderal and multizonal species (including several aliens) that have well adapted to human disturbance, and have partially replaced the typical riverine plants, iv) wide spread of eutrophic aquatic species, and rarefaction of those species that are more sensitive to eutrophication and water pollution. The dataset and the overview reported in this study can be useful for future research, with a special focus on a better naturalistic management of the urban river ecosystem, and the conservation of the floristic heritage within the city of Rome.